Voir, entendre et sentir un événement — quelques observations sur la traduction polonaise des constructions avec verbes de perception - Cook, Jadwiga (Neophilologica, 2014)
The object of our study is French constructions with the perceptive verbs voir, entendre and sentir and their translations into Polish. Those verbs take three types of object: (1) a subordinate clause introduced by que, (2) a noun phrase with a relative clause introduced by qui, and (3) an infinitive clause. Hence, the perception of an event can be moderated by the three different constructions. The differences between these structures are not only syntactic, visible at first glance, but also semantic. The first two structures have an equivalent in Polish, but the third is absent from the target language. Our aim was to verify if the differences between the analyzed structures are visible in their Polish translations and to see what the choices made by the translators could have depend on (the structure, the verb itself or the meaning).